Faktor Penghambat Implementasi Proyek Transportasi Masal berbasis Rel di Surabaya dengan Skema Kerjasama Pemerintah dengan Badan Usaha - Erfandi Zen Variamen; Mohammad Arif Rohman (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
Public Private Partnership (PPPs) is one of the financing solutions in fulfilling infrastructure development for better public services. The rapid rate of population growth in the city of Surabaya is a challenge in developing transportation infrastructure. The alternative strategy is to revive rail-based mass transportation or called Tram. The purpose of this study is to determine the barriers in the implementation of the PPP scheme fo the Tram project. The research variables were obtained from literature review and were divided into 6 groups, namely Social, Legal, Economic, Environmental, Political, and Technology (SLEEPT). The research data was acquired based on four experts’ opinion in this area. Relative Important Index (RII), Confidence Interval (CI), and Pareto Diagram were employed to analyse the data. According to Pareto Diagram (81%), it was found that the economic variable had the two highest indicators, namely